Cell Type-Specific Survey of Epigenetic Modifications by Tandem Chromatin Immunoprecipitation Sequencing - Mari Mito (Nature Portfolio, 2018)
Abstract The nervous system of higher eukaryotes is composed of numerous types of neurons and glia that together orchestrate complex neuronal responses. However, this complex pool of cells typically poses analytical challenges in investigating gene expression profiles and their epigenetic basis for specific cell types. Here, we developed a novel method that enables cell type-specific analyses of epigenetic modifications using tandem chromatin immunoprecipitation sequencing (tChIP-Seq). FLAG-tagged histone H2B, a constitutive chromatin component, was first expressed in Camk2a-positive pyramidal cortical neurons and used to purify chromatin in a cell type-specific manner. Subsequent chromatin immunoprecipitation using antibodies against H3K4me3—a chromatin modification mainly associated with active promoters—allowed us to survey the histone modifications in Camk2a-positive neurons. Indeed, tChIP-Seq identified hundreds of H3K4me3 modifications in promoter regions located upstream of genes associated with neuronal functions and genes with unknown functions in cortical neurons. tChIP-Seq provides a versatile approach to investigating the epigenetic modifications of particular cell types in vivo.